2014
DOI: 10.1007/s00592-014-0681-0
|View full text |Cite
|
Sign up to set email alerts
|

Xenin-25[Lys13PAL]: a novel long-acting acylated analogue of xenin-25 with promising antidiabetic potential

Abstract: These data indicate that sustained administration of a stable analogue of xenin-25 exerts a spectrum of beneficial metabolic effects in high-fat-fed mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 25 publications
5
40
0
2
Order By: Relevance
“…However, further investigations, including euglycaemic-hyperinsulinaemic clamps, glucose uptake and gene and protein expression studies, are required to fully address the molecular mechanisms underpinning this benefit. Somewhat surprisingly, at the dose tested, (DAla 2 )GIP/xenin-8-Gln had no effect on energy intake, although similar observations have been reported previously with xenin-based drugs [38]. This limited satiety effect presumably reflects the requirement of supraphysiological doses of xenin to impart appetite-suppressive effects [10].…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…However, further investigations, including euglycaemic-hyperinsulinaemic clamps, glucose uptake and gene and protein expression studies, are required to fully address the molecular mechanisms underpinning this benefit. Somewhat surprisingly, at the dose tested, (DAla 2 )GIP/xenin-8-Gln had no effect on energy intake, although similar observations have been reported previously with xenin-based drugs [38]. This limited satiety effect presumably reflects the requirement of supraphysiological doses of xenin to impart appetite-suppressive effects [10].…”
Section: Resultssupporting
confidence: 76%
“…However, normalisation of blood glucose levels, as clearly demonstrated in both (DAla 2 )GIPand (DAla 2 )GIP/xenin-8-Gln-treated mice, has also been shown to independently restore GIP insulin-secretory function in type 2 diabetes [5,6]. In addition, we have already confirmed that xenin has significant glucose-lowering activity independent of the GIP receptor [38]. Therefore, further studies are required to systematically assess the direct and indirect beneficial effects of (DAla 2 )GIP/xenin-8-Gln in restoring GIP action in type 2 diabetes.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…injection of vehicle alone (0.9% NaCl w/v). The dosage of 25 nmol/kg was chosen based on previous studies of the effects of Xenin‐25[Lys(13)PAL] on metabolic endpoints . Injections were administered daily at 3:00 pm to avoid potentially confounding effects of injection and restraint stress, and acute drug effects, on behavioural testing, which was performed in the morning.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma xenin concentrations are increased by meal ingestion or sham feeding in humans, suggesting that vagal reflexes stimulate xenin release from the duodenal mucosa [68]. The infusion of low concentrations (4–12 pmol/kg) of xenin to humans delays gastric emptying, inhibits GLP-1 release, and causes mild diarrhea [69;70]. Since RYGB obesity surgery diminishes exogenous xenin-associated diarrhea and the inhibition of GLP-1 release in response to liquid meal, duodenal xenin signals may significantly activate unknown neural pathways [71*].…”
Section: Tuft Cellsmentioning
confidence: 99%